2018
DOI: 10.1158/1078-0432.ccr-17-1090
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation and Consensus Molecular Subtypes 2 and 3 Are Independently Associated with Reduced Immune Infiltration and Reactivity in Colorectal Cancer

Abstract: mutation is a common canonical mutation in colorectal cancer, found at differing frequencies in all consensus molecular subtypes (CMS). The independent immunobiological impacts of RAS mutation and CMS are unknown. Thus, we explored the immunobiological effects of mutation across the CMS spectrum. Expression analysis of immune genes/signatures was performed using The Cancer Genome Atlas (TCGA) RNA-seq and the KFSYSCC microarray datasets. Multivariate analysis included status, CMS, tumor location, MSI status, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 46 publications
5
88
0
Order By: Relevance
“…These cells in turn promote and maintain tumor growth and metastasis. Several studies identified that Kras G12D or Kras G12V mutation contributes to T cell differentiation in colorectal and lung cancer cells . Our previous studies also found that Kras G12D mutation is associated with high Tregs infiltration in resectable pancreatic cancer tissues .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These cells in turn promote and maintain tumor growth and metastasis. Several studies identified that Kras G12D or Kras G12V mutation contributes to T cell differentiation in colorectal and lung cancer cells . Our previous studies also found that Kras G12D mutation is associated with high Tregs infiltration in resectable pancreatic cancer tissues .…”
Section: Discussionsupporting
confidence: 61%
“…Several studies identified that Kras G12D or Kras G12V mutation contributes to T cell differentiation in colorectal and lung cancer cells. 13,31 Our previous studies also found that Kras G12D mutation is associated with high Tregs infiltration in resectable pancreatic cancer tissues. 14 However, the potential correlation of Kras mutation and T cell subsets is still unclear in advanced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 84%
“…CMS4 patients have poorer prognosis and perhaps need more aggressive treatment, and they show limited benefit from Oxaliplatin (Song et al 2016;Okita et al 2018). Patients with CMS2 or CMS3 may benefit from addition of Bevacizumab (Mooi et al 2018) but are not good candidates for immunotherapy (Becht et al 2016;Lal et al 2018), and anti-EGFR therapy appears to work very well for CMS2 patients but not CMS1 (Okita et al 2018).…”
Section: Gsmp Shiny Appmentioning
confidence: 99%
“…About 20 per cent of patients in the MSS colorectal cancer subgroup develop an immunogenomic signature similar to that in MSI‐H colorectal cancer, despite low mutational burden. There is evidence that activating mutations in the Ras–MAPK pathway are associated with lower expression of this immune gene cluster and immune pathway downregulation. In addition, lymphocytic infiltration, particularly of effector and memory T cells into the tumour, a key indicator of prognosis in colorectal cancer, appears to be independent of MSI status.…”
Section: Microsatellite Instability In Colorectal Cancermentioning
confidence: 99%